PENGARUH MEDIA KOMIK DIGITAL TERHADAP PENGETAHUAN CUCI TANGAN SISWA SEKOLAH DASAR (Jurnal Kesehatan Siliwangi, 2021)
Based on data obtained from Health Research (RISKESDAS) shows the proportion of proper handwashing behavior in the population aged ≥ 10 years in Indonesia is as much as 49.8%. The number has not reached the target set by the Ministry of Health of the Republic of Indonesia by 70%. Hand washing is one of the efforts to prevent diarrhea. According to the Health Profile of Bandung in 2018, the incidence of diarrhea at the age of ≥ 10 years in Sukajadi District increased from 1,325 cases to 1,512 cases of diarrhea. This study aims to find out the influence of digital comic media on handwashing knowledge of elementary school students in MIS Ar-rohmah Bandung. this study uses a pre-eskperimental design with one group pretest – posttest without control, and using total samples sampling techniques. Data has been analyzed by using Paired Sample T-Test. The average score of respondent’s knowledge before being given digital comic media was 78.46. The average handwashing knowledge score after being given digital comic media was 94.35. The value of p value in the respondent's knowledge before and after being given digital comic media is (p=0.000). The average score of handwashing knowledge before and after being given digital comic media. There is a significant influence between the provision of digital comic media to the knowledge of handwashing elementary school students in MIS Ar-Rohmah Bandung.